Mechanical correlates of dyspnea in bronchial asthma. Issue 7 (8th December 2013) - Antonelli, Andrea; Crimi, Emanuele; Gobbi, Alessandro; Torchio, Roberto; Gulotta, Carlo; Dellaca, Raffaele; Scano, Giorgio; Brusasco, Vito; Pellegrino, Riccardo
Abstract: We hypothesized that dyspnea and its descriptors, that is, chest tightness, inspiratory effort, unrewarded inspiration, and expiratory difficulty in asthma reflect different mechanisms of airflow obstruction and their perception varies with the severity of bronchoconstriction. Eighty‐three asthmatics were studied before and after inhalation of methacholine doses decreasing the 1‐sec forced expiratory volume by ~15% (mild bronchoconstriction) and ~25% (moderate bronchoconstriction). Symptoms were examined as a function of changes in lung mechanics. Dyspnea increased with the severity of obstruction, mostly because of inspiratory effort and chest tightness. At mild bronchoconstriction, multivariate analysis showed that dyspnea was related to the increase in inspiratory resistance at 5 Hz ( R 5 ) ( r 2  = 0.10, P  = 0.004), chest tightness to the decrease in maximal flow at 40% of control forced vital capacity, and the increase in R 5 at full lung inflation ( r 2  = 0.15, P  = 0.006), inspiratory effort to the temporal variability in R 5‐19 ( r 2  = 0.13, P  = 0.003), and unrewarded inspiration to the recovery of R 5 after deep breath ( r 2  = 0.07, P  = 0.01). At moderate bronchoconstriction, multivariate analysis showed that dyspnea and inspiratory effort were related to the increase in temporal variability in inspiratory reactance at 5 Hz ( X 5 ) ( r 2  = 0.12, P  = 0.04 and r 2 = 0.18, P  < 0.001, respectively), and unrewarded inspiration to the decrease in X 5 at maximum lung inflation ( r 2  = 0.07, P  = 0.04). We conclude that symptom perception is partly explained by indexes of airway narrowing and loss of bronchodilatation with deep breath at low levels of bronchoconstriction, but by markers of ventilation heterogeneity and lung volume recruitment when bronchoconstriction becomes more severe. Abstract : e00166 In asthma, respiratory symptom perception is qualitatively different depending on the level of bronchoconstriction. During the early phases of an attack dyspnea and its descriptors appear to be related to the severity of airway narrowing and loss of bronchodilatation with deep breath, whereas when narrowing worsens they depend on more profound changes in lung periphery as suggested by increased ventilation heterogeneity and reduced lung volume recruitment with breathing.